Тяжелые металлы в подземных водах Харьковской области и их влияние на окружающую среду и здоровье населения - Прибылова, В.Н.; Pribylova, V. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2008)
Рассмотрены вопросы качества питьевой воды и изучения влияния тяжелых металлов в подземных водах на состояние окружающей среды. Проанализировано возможные последствия и влияние тяжелых металлов в подземных водах на организм человека. Сделана обработка полученных результатов химического анализа воды территории харьковской области. На базе этого построены графики содержания тяжелых металлов в пробах воды. In this article the problems of potable water’s quality were investigated. It was considered the influence of heavy metals on the environmental state in underground water. The possible results of the heavy metals influence in the underground water on the mans organism were analyses. The obtained results of the waters chemical composition on the territory of Kharkov region were worked up. The charts of heavy metals composition in the water samples were made on the basis of the results.
Heavy metals in underground water of kharkov region and their influence on the enviroment and peoples health
Keywords: загрязнение окружающей среды; подземные воды; тяжелые металлы; здоровье населения; Харьковская область; environmental pollution; underground water; heavy metals; peoples health; Kharkov region